Heat load development and heat map sensitivity analysis for civil aero-engines - Ebrahimi, Alireza; Jafari, Soheil; Nikolaidis, Theoklis (MDPI, 2024)
The design complexity of the new generation of civil aero-engines results in higher demands on engines’ components, higher component temperatures, higher heat generation, and, finally, critical thermal management issues. This paper will propose a methodological approach to creating physics-based models for heat loads developed by sources, as well as a systematic sensitivity analysis to identify the effects of design parameters on the thermal behavior of civil aero-engines. The ranges and levels of heat loads generated by heat sources (e.g., accessory gearbox, bearing, pumps, etc.) and the heat absorption capacity of heat sinks (e.g., engine fuel, oil, and air) are discussed systematically. The practical research challenges for thermal management system design and development for the new and next generation of turbofan engines will then be addressed through a sensitivity analysis of the heat load values as well as the heat sink flow rates. The potential solutions for thermal performance enhancements of propulsion systems will be proposed and discussed accordingly.
Keywords: thermal management system; heat loads; aero-engines